2011
DOI: 10.1002/cphc.201100767
|View full text |Cite
|
Sign up to set email alerts
|

Large Gadolinium Nitride Cluster Encapsulated inside a Non‐IPR Carbon Cage: A Theoretical Characterization on Gd3N@C78

Abstract: Dedicated to Professor Shigeru Nagase on the occasion of his 65th birthday With metal atoms or clusters entrapped in their inner spaces, endohedral metallofullerenes (EMFs) are viewed as unique compounds with a variety of potential applications. [1][2][3][4][5][6][7][8][9][10] These EMFs are commonly divided into several forms by virtue of the encapsulated moieties.[8] The tri-metallic nitride templated endohedral metallofullerenes (TNT EMFs) often attract much attention due to their high stability and yield r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
1
7
0
1
Order By: Relevance
“…For YSc 2 N@C 78 , conversely, the isomer with the lowest energy also has a large HOMO‐LUMO gap (1.37 eV) and is a classical, but non‐IPR cage, C 78 :22010 with two pentagon adjacencies. The same cage has been reported as the parent in Gd 3 N@C 78 , Y 3 N@C 78 , and GdSc 2 N@ normalC78 [13c] ; in these cases, as for YSc 2 N, the central TN is larger than Sc 3 N. The isomer with the second lowest energy is nonclassical but lies only 1.8 kcal mol −1 higher, so could be expected to have significant population in an equilibrium mixture at 1000 K. LaSc 2 N@C 78 is predicted to have the same most favored cage as YSc 2 N@C 78 , but a second isomer based on a (different) nonclassical cage ( normalC781h:185809) that also has two pentagon adjacencies, and lies 9.0 kcal mol −1 above the best classical isomer.…”
Section: Resultssupporting
confidence: 64%
“…For YSc 2 N@C 78 , conversely, the isomer with the lowest energy also has a large HOMO‐LUMO gap (1.37 eV) and is a classical, but non‐IPR cage, C 78 :22010 with two pentagon adjacencies. The same cage has been reported as the parent in Gd 3 N@C 78 , Y 3 N@C 78 , and GdSc 2 N@ normalC78 [13c] ; in these cases, as for YSc 2 N, the central TN is larger than Sc 3 N. The isomer with the second lowest energy is nonclassical but lies only 1.8 kcal mol −1 higher, so could be expected to have significant population in an equilibrium mixture at 1000 K. LaSc 2 N@C 78 is predicted to have the same most favored cage as YSc 2 N@C 78 , but a second isomer based on a (different) nonclassical cage ( normalC781h:185809) that also has two pentagon adjacencies, and lies 9.0 kcal mol −1 above the best classical isomer.…”
Section: Resultssupporting
confidence: 64%
“…[33] It was also recently published that the low-spin state in the case of the related compound Gd 3 N@C 78 is 4.5 meV ( % 0.1 kcal mol À1 ) lower in energy than the highspin state. [34] All calculations reported here have been performed considering the antiferromagnetic coupling (i.e., S = 7 = 2 ). In practice, the analytical vibrational frequencies for the TSs of the gadolinium-based EMFs were not calculated due to the high computational cost and SCF convergence difficulties related with the high number of unpaired electrons, and based on the similarities of the TS structures with those of the other metal clusters.…”
Section: Methodsmentioning
confidence: 99%
“…The difference in energy between the latter two configurations was found to be extremely low (0.1 kcal mol −1 ) 33. It was also recently published that the low‐spin state in the case of the related compound Gd 3 N@C 78 is 4.5 meV (≈0.1 kcal mol −1 ) lower in energy than the high‐spin state 34. All calculations reported here have been performed considering the antiferromagnetic coupling (i.e., S =7/2).…”
Section: Methodsmentioning
confidence: 99%
“…[57][58][59] We note that CEP-4G basis set has been used in previous studies of EMFs and was shown to perform well, and a few examples are the studies of Dy 2 @C 100 , 60 Yb@C 76 , 61 Gd 3 N@C 78 (ref. 62) and Gd 2 @C 98 . 63 The calculations with BS2 basis set gives an RMSD of 10.56 ppm using BHandHLYP method, which is 4.55 ppm larger than that at the BS1 level, suggesting CEP-4G may be not a good choice for an open-shell molecular system.…”
Section: Nmr Propertymentioning
confidence: 98%